2020
DOI: 10.5222/mmj.2020.96646
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Temperament Characteristics On Depression-Anxiety Level And Quality Of Life In Infertile Women

Abstract: Objective: It is known that the risk of anxiety disorders and depression in infertile women increases and their quality of life deteriorates. Temperamental characteristics are considered as predictors of mood disorders. The aim of this study was to investigate temperamental characteristics in infertile women and their effects on depression and anxiety levels, and the quality of life, and to reveal the differences and level of relationship compared to healthy women. Method: Fourty-four female patients with prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Thus, they may also in uence the degree of depression and anxiety and other manifestations of emotional dysregulations caused by infertility-related stressors [7]. In support of this, the sole study so far examining the direct relationship between infertility and affective temperaments found that hyperthymic temperament is protective against anxiety and depression in infertile women [59]. Likewise, no studies have examined the relationship between infertility treatment outcomes and affective temperaments so far.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may also in uence the degree of depression and anxiety and other manifestations of emotional dysregulations caused by infertility-related stressors [7]. In support of this, the sole study so far examining the direct relationship between infertility and affective temperaments found that hyperthymic temperament is protective against anxiety and depression in infertile women [59]. Likewise, no studies have examined the relationship between infertility treatment outcomes and affective temperaments so far.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, very few studies have so far investigated the relationship between temperament and infertility or the success of infertility treatments. The sole study so far examining the direct relationship between infertility and affective temperaments found that hyperthymic temperament is protective against anxiety and depression in infertile women 66 . Likewise, no studies have examined the relationship between infertility treatment outcomes and affective temperaments so far.…”
Section: Discussionmentioning
confidence: 99%
“… 29–31 The evaluation of affective temperament seems to determine which of the infertile women are more prone to the development of depression and anxiety. 32 Moreover, recent research in a group of gestational diabetes patients showed promising data regarding the association between affective temperament and the development of gestational diabetes, as well as disturbances in glycemic metabolism in this group of patients. 33 Hence, TEMPS-A might be of great utility in determining patients with greater susceptibility of pregnancy complications.…”
Section: Introductionmentioning
confidence: 98%